2019
DOI: 10.1055/s-0039-1679919
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen Hepatotoxicity

Abstract: Acetaminophen (APAP) is one of the most popular and safe pain medications worldwide. However, due to its wide availability, it is frequently implicated in intentional or unintentional overdoses where it can cause severe liver injury and even acute liver failure (ALF). In fact, APAP toxicity is responsible for 46% of all ALF cases in the United States. Early mechanistic studies in mice demonstrated the formation of a reactive metabolite, which is responsible for hepatic glutathione depletion and initiation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
179
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(187 citation statements)
references
References 180 publications
4
179
1
3
Order By: Relevance
“…Although the results obtained using this experimental animal model and in the human clinical setting have broadly been consistent with respect to the DILI risk associated with particular drugs, the model differs from humans in several respects. For example, the injury occurs within 24 hr of drug administration and liver histology is characterized by an infiltration of neutrophils in this animal model (Ramachandran and Jaeschke, 2019), whereas clinical DILI is generally characterized by delayed onset (Wang et al, 2018) and mononuclear leukocyte infiltration. However, even though the model does not perfectly mimic DILI in humans, it is considered useful for the screening of candidate drugs for potential liver toxicity and/or exploring the pathologic mechanism of any liver injury induced.…”
Section: Introductionmentioning
confidence: 92%
“…Although the results obtained using this experimental animal model and in the human clinical setting have broadly been consistent with respect to the DILI risk associated with particular drugs, the model differs from humans in several respects. For example, the injury occurs within 24 hr of drug administration and liver histology is characterized by an infiltration of neutrophils in this animal model (Ramachandran and Jaeschke, 2019), whereas clinical DILI is generally characterized by delayed onset (Wang et al, 2018) and mononuclear leukocyte infiltration. However, even though the model does not perfectly mimic DILI in humans, it is considered useful for the screening of candidate drugs for potential liver toxicity and/or exploring the pathologic mechanism of any liver injury induced.…”
Section: Introductionmentioning
confidence: 92%
“…Acetaminophen (APAP, also known as paracetamol) is one of the most widely used analgesic or antipyretic drugs, and is safe when used at therapeutic doses. However, overdose of APAP causes liver damage in a dosedependent manner, and in severe cases, results in acute liver failure 1 . Once acute liver failure occurs, liver transplantation is the only established life-saving procedure 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, additional therapeutic approaches for APAP-induced hepatotoxicity are required and research is needed to understand the underlying mechanism. An enormous number of studies on the mechanism underlying APAP-induced hepatotoxicity have been reported so far, and they have clarified the mechanism to some extent 1 . For instance, APAP is metabolized to N-acetyl-p-benzoquinone imine (NAPQI) in hepatocytes by cytochrome P450 2E1 (CYP2E1) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Acetaminophen overdose toxicity is the most common cause of acute liver failure and occurs because an acetaminophen metabolite (N-Acetyl-p-benzoquinone imine) causes glutathione depletion and mitochondrial protein adducts which in turn lead to elevated oxidant stress and GSK-3ÎČ, JNK, and Bax signaling. The ensuing mPT, ROS formation, and cell death can be substantially alleviated by CsA, NIM811, or Cyp D knockout although the degree of protection also depends on acetaminophen dose [158][159][160]. Chronic alcohol consumption in rodents was found to increase Cyp D, cause mitochondrial swelling, and sensitize mitochondria to mPT in the liver, although mitochondrial depolarization and hepatocyte apoptosis were not sensitive to CsA or Cyp D knockout [161][162][163].…”
Section: Cyclophilin Involvement In Cellular Injurymentioning
confidence: 98%